Pengembangan Aplikasi Pelatihan Otot Mata Penderita Miopia Menggunakan Metode Bates dan Teknologi Virtual Reality - Mukhammad Sharif Hidayatulloh; Komang Candra Brata; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The common treatment for the myopia is by using the glasses, the other ways to cure this problem is doing lasiik surgery, but it takes large amount of financial so only people who have good financial can do this solution. The bates method which have found by Dr. William Horatio Bates 100 years ago was easy and can be used by everyone to cure myopia. The bates method has implemented to an application which using virtual reality technology, this implementation have a purpose to train eyebrow muscle eye easily and independently. The using of gyroscope sensor in smartphone and google vr sdk support eyebrow muscle eye training on bates method. The simulation in this training using the green pointer which move based on training technique. The user using this application in period 30 days and 5-10 minutes training duration each day. The measurement of myopia scale done on the first day and 5 times in period 30 days with interval 6 day using in-app features. The result of effectiveness testing for 12 respondent show the avarage decrease of myopia scale is 0.22D. This result come near with the result of Hildeth's research in 1947 that show result 0.25D. This successfull testing show that virtual reality implementation is effective with bates method.